Study on Control of First Order Plus Delay Using Smith Predictor - Ahmed, Saad A (Al-Nahrain Journal of Science, 2018)
This paper presents the implementation of Smith predictor structure for the control of a first order plus delay time process. Water heater for vacuum distillation apparatus is studied, the open loop transfer function shows a first order plus delay time. The control system is analyzed using open loop Bode plot and root locus method through “sisotool” in MATLAB control tool box. The Smith predictor control design carried out using MATLAB (7.11.0) command windows. The controller gain is found to be 96.3 and the integral time 256.4